A 5xxx series aluminum alloy grain boundary metallographic etchant and grain size display method
By preparing corrosive agents of potassium permanganate, hydrofluoric acid and sulfuric acid, priority corrosion of 5xxx series aluminum alloy grain boundaries under conventional microscopes, solving the problem of time-consuming and costly detection in the prior art, and achieving fast and simple grain boundary observation and grain size rating.
Patent Information
- Application Number
- CN202510008619.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to quickly and easily observe the grain boundary structure of 5xxx aluminum alloy under conventional black and white field of view, and the detection method of anode coating plus polarized light is time-consuming and costly.
A 5xxx aluminum alloy grain boundary metallographic corrosion agent is provided, and the composition includes potassium permanganate, hydrofluoric acid and sulfuric acid. By preparing the corrosion agent for metallographic detection under a conventional optical microscope, the effect of preferential grain boundary corrosion is achieved.
This method can clearly and completely observe the grain boundaries and grain structure of the aluminum alloy without additional light sources, simplifying the metallographic corrosion process, reducing experimental costs, and improving detection efficiency.
Smart Images

Figure CN119776830A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal detection, and in particular relates to a 5xxx series aluminum alloy grain boundary metallographic etching agent and a grain size display method. Background Art
[0002] 5xxx series aluminum alloys use magnesium as the main alloying element (Al-Mg-Mn). Due to the difficulty of nucleation of the precipitation phase, the mechanical strength mainly comes from cold deformation and supersaturated solid solution of Mg atoms. Because there is no precipitation phase inside the material and the structure is uniform, it has excellent corrosion resistance and is also called rust-proof aluminum. Due to its high fatigue strength, excellent weldability, and good surface treatment performance, it has been widely used in the field of rail passenger car manufacturing. Among them, 5083 and 5086 are particularly widely used in rail passenger cars. This is because a small amount of Mn and Cr elements are added to the chemical composition of 5083 and 5086 aluminum alloys. Adding Cr elements can hinder the recrystallization or recrystallization grain growth after extrusion and refine the grains; adding Mn elements can ensure the solid solution strengthening effect of the alloy. At the same time, Mn elements can prevent the precipitation of Al3Mg2 phase along the grain boundary, reduce the activity of impurity Fe, and improve corrosion resistance, resulting in the 5083 and 5086 metallographic structure The grain boundary is difficult to corrode. In the prior art, the grain boundaries of aluminum alloys are mainly displayed by etching with NaOH aqueous solution or HF+HCl+HNO3 mixed acid. However, for 5xxx aluminum alloys with outstanding anti-rust effect, the metallographic structure obtained by etching the aluminum alloy with the above-mentioned corrosive agents is blurred and the grain boundary structure cannot be displayed. Therefore, anodic coating plus polarized light is usually used to observe the grain boundaries and grain size. The coating plus polarized light detection method is not only time-consuming, but also requires polarized light observation equipment, which increases sample preparation and laboratory costs. Therefore, there is an urgent need for a simple and fast, no additional light source, suitable for observing the grain boundaries of 5xxx aluminum alloys under conventional black and white viewing fields. New corrosive agents and grain size display methods are unresolved problems. Summary of the invention
[0003] The purpose of the present invention is to solve the difficulties in the above-mentioned technology and provide a 5xxx series aluminum alloy grain boundary metallographic etching agent and a grain size display method. The new metallographic etching technology can achieve the effect of grain boundaries corroding before grains under a conventional black and white grayscale microscope without an additional light source, effectively reducing the metallographic etching process and shortening the corrosion time. The etching agent to be prepared is a commonly used etching solution in the laboratory. The metallographic structure detection does not require anodic coating and polarized light to observe clear and complete grain boundaries and grain structure morphology, thereby accurately evaluating the grain size grade.
[0004] To achieve the above-mentioned purpose of the invention, the present invention provides a 5xxx series aluminum alloy grain boundary metallographic etching agent, which comprises 1-2g of potassium permanganate, 1-2ml of hydrofluoric acid, 14-20ml of sulfuric acid, and 100ml of ultrapure water, wherein the mass concentration of hydrofluoric acid is not less than 40%, the mass concentration of sulfuric acid is 95%-98%, and the conductivity of ultrapure water is ≤10μS / cm.
[0005] The present invention also provides a method for displaying the grain size of a 5xxx series aluminum alloy, using the above-mentioned 5xxx series aluminum alloy grain boundary metallographic etchant, comprising the following steps:
[0006] Step 1, prepare a mixed corrosive agent of 1-2 g potassium permanganate, 1-2 ml hydrofluoric acid, 14-20 ml sulfuric acid, and 100 ml ultrapure water;
[0007] Step 2, sample preparation: use a metallographic cutting machine to take a metallographic sample of 5xxx series aluminum alloy;
[0008] Step 3, inlaying: placing the 5xxx series aluminum alloy metallographic sample in an inlay mold sleeve, adding a hot-mounting phenolic resin inlay material, and inlaying the sample;
[0009] Step 4: Grinding: Place the prepared sample on a metallographic grinding and polishing machine for grinding. Use sandpaper for grinding. The subsequent process should be polished to eliminate the grinding marks of the previous process.
[0010] Step 5: Mechanical polishing: Place the polished sample on a grinding and polishing machine for polishing. Use a long-pile cloth for polishing. The polishing time is 8s to 15s.
[0011] Step 6, corrosion: place the mechanically polished sample in a corrosion reagent for 20s to 30s;
[0012] Step 7, rinsing: the corroded surface of the sample after mechanical polishing is cleaned with water and anhydrous ethanol in turn, and dried;
[0013] Step 8: Metallographic examination: Place the corroded sample under a conventional optical microscope to observe the metallographic structure morphology.
[0014] Furthermore, in the step 2, water-polished non-silicon sandpaper is preferably used, and the grits of the sandpaper are 180#, 400#, 800#, 1200#, and 2000#, respectively.
[0015] Furthermore, the diamond polishing agent used in the polishing in step three has a particle size of 1.5 μm, and the rotation speed of the mechanical polishing is 900 r / min.
[0016] Advantages of the present invention:
[0017] 1. The new metallographic corrosion technology for 5xxx series aluminum alloys of the present invention has the advantages of good corrosion effect, fewer sample preparation steps, and simple operation. The grain boundaries of the aluminum alloy are clearly observed, the grain size is complete, and the grain size rating is easy. There is no black film formed by conventional acid and alkali corrosive agents on the surface of the sample, and the technical advantage of not requiring polarized light treatment for observing the metallographic structure under a conventional optical microscope is overcome. The detection method of the present invention is simple to operate, has a high success rate, and good reproducibility. It can adapt to the detection of large quantities of samples and improve work efficiency.
[0018] 2. The chemical reagents used to prepare the metallographic etchant of the present invention are all commonly used reagents, which are easy to obtain on the market, low in cost, have fewer requirements on detection conditions and detection equipment, are easy to operate, and are convenient for wide promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic diagram of the metallographic structure of the polishing and etching 100 times of Example 1 of the present invention.
[0020] Figure 2 This is a schematic diagram of the metallographic structure of the polishing and etching 100 times of Example 2 of the present invention.
[0021] Figure 3 This is a schematic diagram of the metallographic structure of the polishing and etching 200 times of Example 2 of the present invention.
[0022] Figure 4 This is a schematic diagram of the metallographic structure of the polishing and etching 100 times of Example 3 of the present invention.
[0023] Figure 5 This is a schematic diagram of the metallographic structure of the fourth embodiment of the present invention after polishing and etching 100 times.
[0024] Figure 6 This is a schematic diagram of the metallographic structure of the polishing and etching 100 times of Example 5 of the present invention.
[0025] Figure 7 This is a schematic diagram of the metallographic structure of the polishing and etching 200 times of Example 5 of the present invention.
[0026] Figure 8 This is a schematic diagram of the metallographic structure of the polishing and etching 100 times of Example 6 of the present invention.
[0027] Fig. 9 This is a schematic diagram of the metallographic structure of the polishing and etching 100 times of Example 7 of the present invention.
[0028] Fig.10 This is a schematic diagram of the metallographic structure of the polishing and etching 100 times of Example 8 of the present invention.
[0029] Fig.11 This is a schematic diagram of the metallographic structure of the polishing and etching 200 times of Example 8 of the present invention.
[0030] Fig.12 This is a schematic diagram of the metallographic structure of the polishing and etching 100 times of Example 9 of the present invention.
[0031] Fig.13 This is a schematic diagram of the metallographic structure of the anode coating of Comparative Example 1 of the present invention at 100 times the size.
[0032] Fig.14 This is a schematic diagram of the metallographic structure of the anode coating of Comparative Example 2 of the present invention at 100 times the size.
[0033] Fig.15 This is a schematic diagram of the metallographic structure of the conventional etching process 100 times that of comparative example 3 of the present invention. DETAILED DESCRIPTION
[0034] The present invention provides a 5xxx series aluminum alloy grain boundary metallographic etchant, which is composed of the following components:
[0035] The etchant is obtained by mixing a mixed aqueous solution of potassium permanganate (KMnO4), hydrofluoric acid (HF), and sulfuric acid (H2SO4), wherein the mixed etchant comprises: 1-2g potassium permanganate, 1-2ml hydrofluoric acid, 14-20ml sulfuric acid, and 100ml ultrapure water, wherein the mass concentration of hydrofluoric acid is not less than 40%, the mass concentration of sulfuric acid is 95%-98%, and the conductivity of ultrapure water is ≤10μS / cm.
[0036] Solvent selection mechanism: F in hydrofluoric acid - The atomic radius is small and the permeability is strong. It can better penetrate and destroy the oxide film. Al2O3+6HF→2AlF3+3H2O can make the aluminum alloy surface without the protection of the oxide film exposed to the strong acid environment. Because the grain boundary energy is high and there is a layer of electronegative area on the grain boundary, it is easy to adsorb impurity elements, which will corrode first. At the same time, the coloring ion is It is a highly electronegative ion. The ion is unstable and reacts with magnesium and aluminum, 2KMnO4+3Mg→2MnO2+3Mg 2+ +2K + 、2KMnO4+2Al→2MnO2+2Al 3+ , generating precipitation to accelerate intergranular corrosion, and a quantitative coloring effect occurs on the surface of the aluminum alloy. The above reaction needs to be carried out under acidic conditions, preferably adding sulfuric acid as its catalyst. This solution corrosion mechanism will obtain the aluminum alloy intergranular corrosion agent desired by the present invention.
[0037] Technical barriers: 5xxx series aluminum alloys are aluminum alloys with Mg as the main additive element. Due to its excellent corrosion resistance, it is also called rust-proof aluminum alloy. Using daily acidic corrosives such as Keller reagent, the ionic Mg and Mn in the surface strengthening phase of aluminum alloys are difficult to react with F in the acidic corrosives. - 、NO3 - If the reaction does not extend to the grain boundary with weak free energy, it will be difficult to show the grain boundary; anodic coating is an electrolytic process that uses the galvanic redox reaction of metal in the electrolyte to form a closed loop and form an oxide film on the metal surface. The oxide film forms a thickness difference and coloring on the grain structure under the metal. After the sample is treated with anodic coating, the ideal tissue image can be obtained by using a polarized light microscope and sensitive color. This method has a complicated process, high film thickness requirements, no additional light source, and cannot be observed under a conventional black and white grayscale microscope, resulting in low metallographic corrosion efficiency of 5xxx series aluminum alloys and high experimental costs.
[0038] This technical invention uses a new mixed corrosive agent to preferentially dissolve and color the grain boundaries with weak free energy on the surface of aluminum alloy, making full use of the chemical corrosion mechanism to accelerate and promote the corrosion mechanism of the corrosive agent on the grain boundaries of 5xxx series rust-proof aluminum alloy in this technical invention. It breaks the technical barrier that 5xxx series aluminum alloy must use anodic coating, shortens the metallographic preparation process, and obtains high-quality grain size rating images.
[0039] In order to achieve the above technical objectives, the implementation steps of the grain size display method of the present invention are as follows:
[0040] Embodiment 1 scheme:
[0041] Step 1: prepare a new mixed corrosive agent: 1g potassium permanganate + 1ml hydrofluoric acid + 14ml sulfuric acid + 100ml ultrapure water;
[0042] Step 2, sample preparation: use a metallographic cutting machine to take a 5083-H111 aluminum alloy metallographic sample;
[0043] Step 3, inlaying: placing the 5083-H111 aluminum alloy metallographic sample in an inlay mold sleeve, adding hot-inlay phenolic resin inlay material, and inlaying the sample;
[0044] Step 4, grinding: Place the prepared sample on a metallographic grinding and polishing machine for grinding. For aluminum alloy, water-grinded non-silicon sandpaper is preferred. The grits of the grinding sandpaper are 180#, 400#, 800#, 1200#, and 2000#. The subsequent process should be polished to eliminate the wear marks of the previous process;
[0045] Step 5, mechanical polishing: Place the polished sample on a grinding and polishing machine for polishing, use a long-pile cloth for polishing, polish for 8s to 15s, use a diamond polishing agent with a particle size of 1.5μm, and a polishing speed of 900r / min;
[0046] Step 6, corrosion: place the mechanically polished sample in a corrosion reagent for 20s to 30s;
[0047] Step 7, rinsing: the corroded surface of the sample after mechanical polishing is cleaned with water and anhydrous ethanol in turn, and dried;
[0048] Step 8: Metallographic examination: Place the corroded sample under a conventional optical microscope to observe the metallographic structure morphology. Figure 1 Shown is a schematic diagram of the metallographic structure of this scheme at 100 times.
[0049] Embodiment 2 scheme:
[0050] Step 1: prepare a new mixed corrosive agent: 2g potassium permanganate + 1ml hydrofluoric acid + 16ml sulfuric acid + 100ml ultrapure water;
[0051] Step 2, sample preparation: use a metallographic cutting machine to take a 5083-H111 aluminum alloy metallographic sample;
[0052] Step 3, inlaying: placing the 5083-H111 aluminum alloy metallographic sample in an inlay mold sleeve, adding hot-inlay phenolic resin inlay material, and inlaying the sample;
[0053] Step 4, grinding: Place the prepared sample on a metallographic grinding and polishing machine for grinding. For aluminum alloy, water-grinded non-silicon sandpaper is preferred. The grits of the grinding sandpaper are 180#, 400#, 800#, 1200#, and 2000#. The subsequent process should be polished to eliminate the wear marks of the previous process;
[0054] Step 5, mechanical polishing: Place the polished sample on a grinding and polishing machine for polishing, use a long-pile cloth for polishing, polish for 8s to 15s, use a diamond polishing agent with a particle size of 1.5μm, and a polishing speed of 900r / min;
[0055] Step 6, corrosion: place the mechanically polished sample in a corrosion reagent for 20s to 30s;
[0056] Step 7, rinsing: the corroded surface of the sample after mechanical polishing is cleaned with water and anhydrous ethanol in turn, and dried;
[0057] Step 8: Metallographic examination: Place the corroded sample under a conventional optical microscope to observe the metallographic structure morphology. Figure 2 The figure shows the metallographic structure diagram of this scheme at 100 times magnification. Figure 3Shown is a schematic diagram of the metallographic structure of this scheme at 200 times.
[0058] Embodiment 3 scheme:
[0059] Step 1: prepare a new mixed corrosive agent: 2g potassium permanganate + 2ml hydrofluoric acid + 20ml sulfuric acid + 100ml ultrapure water;
[0060] Step 2, sample preparation: use a metallographic cutting machine to take a 5083-H111 aluminum alloy metallographic sample;
[0061] Step 3, inlaying: placing the 5083-H111 aluminum alloy metallographic sample in an inlay mold sleeve, adding hot-inlay phenolic resin inlay material, and inlaying the sample;
[0062] Step 4, grinding: Place the prepared sample on a metallographic grinding and polishing machine for grinding. For aluminum alloy, water-grinded non-silicon sandpaper is preferred. The grits of the grinding sandpaper are 180#, 400#, 800#, 1200#, and 2000#. The subsequent process should be polished to eliminate the wear marks of the previous process;
[0063] Step 5, mechanical polishing: Place the polished sample on a grinding and polishing machine for polishing, use a long-pile cloth for polishing, polish for 8s to 15s, use a diamond polishing agent with a particle size of 1.5μm, and a polishing speed of 900r / min;
[0064] Step 6, corrosion: place the mechanically polished sample in a corrosion reagent for 20s to 30s;
[0065] Step 7, rinsing: the corroded surface of the sample after mechanical polishing is cleaned with water and anhydrous ethanol in turn, and dried;
[0066] Step 8: Metallographic examination: Place the corroded sample under a conventional optical microscope to observe the metallographic structure morphology. Figure 4 Shown is a schematic diagram of the metallographic structure of this scheme at 100 times.
[0067] Embodiment 4 scheme:
[0068] Step 1: prepare a new mixed corrosive agent: 1g potassium permanganate + 1ml hydrofluoric acid + 14ml sulfuric acid + 100ml ultrapure water;
[0069] Step 2, sample preparation: use a metallographic cutting machine to take a 5083-H321 aluminum alloy metallographic sample;
[0070] Step 3, inlaying: placing the 5083-H321 aluminum alloy metallographic sample in an inlay mold sleeve, adding hot-inlay phenolic resin inlay material, and inlaying the sample;
[0071] Step 4, grinding: Place the prepared sample on a metallographic grinding and polishing machine for grinding. For aluminum alloy, water-grinded non-silicon sandpaper is preferred. The grits of the grinding sandpaper are 180#, 400#, 800#, 1200#, and 2000#. The subsequent process should be polished to eliminate the wear marks of the previous process;
[0072] Step 5, mechanical polishing: Place the polished sample on a grinding and polishing machine for polishing, use a long-pile cloth for polishing, polish for 8s to 15s, use a diamond polishing agent with a particle size of 1.5μm, and a polishing speed of 900r / min;
[0073] Step 6: Corrosion: Place the mechanically polished sample in a corrosive agent for 20s to 30s.
[0074] Step 7, rinsing: the corroded surface of the sample after mechanical polishing is cleaned with water and anhydrous ethanol in turn, and dried;
[0075] Step 8: Metallographic examination: Place the corroded sample under a conventional optical microscope to observe the metallographic structure morphology. Figure 5 Shown is a schematic diagram of the metallographic structure of this scheme at 100 times.
[0076] Embodiment 5 scheme:
[0077] Step 1: prepare a new mixed corrosive agent: 2g potassium permanganate + 1ml hydrofluoric acid + 16ml sulfuric acid + 100ml ultrapure water;
[0078] Step 2, sample preparation: use a metallographic cutting machine to take a 5083-H321 aluminum alloy metallographic sample;
[0079] Step 3, inlaying: placing the 5083-H321 aluminum alloy metallographic sample in an inlay mold sleeve, adding hot-inlay phenolic resin inlay material, and inlaying the sample;
[0080] Step 4, grinding: Place the prepared sample on a metallographic grinding and polishing machine for grinding. For aluminum alloy, water-grinded non-silicon sandpaper is preferred. The grits of the grinding sandpaper are 180#, 400#, 800#, 1200#, and 2000#. The subsequent process should be polished to eliminate the wear marks of the previous process;
[0081] Step 5, mechanical polishing: Place the polished sample on a grinding and polishing machine for polishing, use a long-pile cloth for polishing, polish for 8s to 15s, use a diamond polishing agent with a particle size of 1.5μm, and a polishing speed of 900r / min;
[0082] Step 6: Corrosion: Place the mechanically polished sample in a corrosive agent for 20s to 30s.
[0083] Step 7, rinsing: the corroded surface of the sample after mechanical polishing is cleaned with water and anhydrous ethanol in turn, and dried;
[0084] Step 8: Metallographic examination: Place the corroded sample under a conventional optical microscope to observe the metallographic structure morphology. Figure 6 The figure shows the metallographic structure diagram of this scheme at 100 times magnification. Figure 7 Shown is a schematic diagram of the metallographic structure of this scheme at 200 times.
[0085] Embodiment 6 scheme:
[0086] Step 1: prepare a new mixed corrosive agent: 2g potassium permanganate + 2ml hydrofluoric acid + 20ml sulfuric acid + 100ml ultrapure water;
[0087] Step 2, sample preparation: use a metallographic cutting machine to take a 5083-H321 aluminum alloy metallographic sample;
[0088] Step 3, inlaying: placing the 5083-H321 aluminum alloy metallographic sample in an inlay mold sleeve, adding hot-inlay phenolic resin inlay material, and inlaying the sample;
[0089] Step 4, grinding: Place the prepared sample on a metallographic grinding and polishing machine for grinding. For aluminum alloy, water-grinded non-silicon sandpaper is preferred. The grits of the grinding sandpaper are 180#, 400#, 800#, 1200#, and 2000#. The subsequent process should be polished to eliminate the wear marks of the previous process;
[0090] Step 5, mechanical polishing: Place the polished sample on a grinding and polishing machine for polishing, use a long-pile cloth for polishing, polish for 8s to 15s, use a diamond polishing agent with a particle size of 1.5μm, and a polishing speed of 900r / min;
[0091] Step 6: Corrosion: Place the mechanically polished sample in a corrosive agent for 20s to 30s.
[0092] Step 7, rinsing: the corroded surface of the sample after mechanical polishing is cleaned with water and anhydrous ethanol in turn, and dried;
[0093] Step 8: Metallographic examination: Place the corroded sample under a conventional optical microscope to observe the metallographic structure morphology. Figure 8 Shown is a schematic diagram of the metallographic structure of this scheme at 100 times.
[0094] Embodiment 7 scheme:
[0095] Step 1: prepare a new mixed corrosive agent: 1g potassium permanganate + 1ml hydrofluoric acid + 14ml sulfuric acid + 100ml ultrapure water;
[0096] Step 2, sample preparation: use a metallographic cutting machine to take a 5086-H111 aluminum alloy metallographic sample;
[0097] Step 3, inlaying: placing the 5086-H111 aluminum alloy metallographic sample in an inlay mold sleeve, adding hot-inlay phenolic resin inlay material, and inlaying the sample;
[0098] Step 4, grinding: Place the prepared sample on a metallographic grinding and polishing machine for grinding. For aluminum alloy, water-grinded non-silicon sandpaper is preferred. The grits of the grinding sandpaper are 180#, 400#, 800#, 1200#, and 2000#. The subsequent process should be polished to eliminate the wear marks of the previous process;
[0099] Step 5, mechanical polishing: Place the polished sample on a grinding and polishing machine for polishing, use a long-pile cloth for polishing, polish for 8s to 15s, use a diamond polishing agent with a particle size of 1.5μm, and a polishing speed of 900r / min;
[0100] Step 6: Corrosion: Place the mechanically polished sample in a corrosive agent for 20s to 30s.
[0101] Step 7, rinsing: the corroded surface of the sample after mechanical polishing is cleaned with water and anhydrous ethanol in turn, and dried;
[0102] Step 8: Metallographic examination: Place the corroded sample under a conventional optical microscope to observe the metallographic structure morphology. Fig. 9 Shown is a schematic diagram of the metallographic structure of this scheme at 100 times.
[0103] Embodiment 8 scheme:
[0104] Step 1: prepare a new mixed corrosive agent: 2g potassium permanganate + 1ml hydrofluoric acid + 16ml sulfuric acid + 100ml ultrapure water;
[0105] Step 2, sample preparation: use a metallographic cutting machine to take a 5086-H111 aluminum alloy metallographic sample;
[0106] Step 3, inlaying: placing the 5086-H111 aluminum alloy metallographic sample in an inlay mold sleeve, adding hot-inlay phenolic resin inlay material, and inlaying the sample;
[0107] Step 4, grinding: Place the prepared sample on a metallographic grinding and polishing machine for grinding. For aluminum alloy, water-grinded non-silicon sandpaper is preferred. The grits of the grinding sandpaper are 180#, 400#, 800#, 1200#, and 2000#. The subsequent process should be polished to eliminate the wear marks of the previous process;
[0108] Step 5, mechanical polishing: Place the polished sample on a grinding and polishing machine for polishing, use a long-pile cloth as the polishing cloth, polish for 8s to 15s, use a diamond polishing agent with a particle size of 1.5μm, and a mechanical polishing speed of 900r / min;
[0109] Step 6: Corrosion: Place the mechanically polished sample in a corrosive agent for 20s to 30s.
[0110] Step 7, rinsing: the corroded surface of the sample after mechanical polishing is cleaned with water and anhydrous ethanol in turn, and dried;
[0111] Step 8: Metallographic examination: Place the corroded sample under a conventional optical microscope to observe the metallographic structure morphology. Fig.10 The figure shows the metallographic structure diagram of this scheme at 100 times magnification. Fig.11 Shown is a schematic diagram of the metallographic structure of this scheme at 200 times.
[0112] Embodiment 9 scheme:
[0113] Step 1: prepare a new mixed corrosive agent: 2g potassium permanganate + 2ml hydrofluoric acid + 20ml sulfuric acid + 100ml ultrapure water;
[0114] Step 2, sample preparation: use a metallographic cutting machine to take a 5086-H111 aluminum alloy metallographic sample;
[0115] Step 3, inlaying: placing the 5086-H111 aluminum alloy metallographic sample in an inlay mold sleeve, adding hot-inlay phenolic resin inlay material, and inlaying the sample;
[0116] Step 4, grinding: Place the prepared sample on a metallographic grinding and polishing machine for grinding. For aluminum alloy, water-grinded non-silicon sandpaper is preferred. The grits of the grinding sandpaper are 180#, 400#, 800#, 1200#, and 2000#. The subsequent process should be polished to eliminate the wear marks of the previous process;
[0117] Step 5, mechanical polishing: Place the polished sample on a grinding and polishing machine for polishing, use a long-pile cloth for polishing, polish for 8s to 15s, use a diamond polishing agent with a particle size of 1.5μm, and a polishing speed of 900r / min;
[0118] Step 6: Corrosion: Place the mechanically polished sample in a corrosive agent for 20s to 30s.
[0119] Step 7, rinsing: the corroded surface of the sample after mechanical polishing is cleaned with water and anhydrous ethanol in turn, and dried;
[0120] Step 8: Metallographic examination: Place the corroded sample under a conventional optical microscope to observe the metallographic structure morphology. Fig.12Shown is a schematic diagram of the metallographic structure of this scheme at 100 times.
[0121] Comparative Example 1 Scheme:
[0122] Step 1, preparing an anode coating solution: a mixed solution of fluoroboric acid and water, wherein the mixed solution component ratio is 5g:200ml;
[0123] Step 2, sample preparation: use a metallographic cutting machine to take a 5083-H111 aluminum alloy metallographic sample;
[0124] Step 3, inlaying: placing the 5083-H111 aluminum alloy metallographic sample in an inlay mold sleeve, adding hot-inlay phenolic resin inlay material, and inlaying the sample;
[0125] Step 4, grinding: Place the prepared sample on a metallographic grinding and polishing machine for grinding. For aluminum alloy, water-grinded non-silicon sandpaper is preferred. The grits of the grinding sandpaper are 180#, 400#, 800#, 1200#, and 2000#. The subsequent process should be polished to eliminate the wear marks of the previous process;
[0126] Step 5, mechanical polishing: Place the polished sample on a grinding and polishing machine for polishing, use a long-pile cloth for polishing, polish for 8s to 15s, use a diamond polishing agent with a particle size of 1.5μm, and a polishing speed of 900r / min;
[0127] Step 6, anodic coating: using a voltage-stabilized power supply, placing the mechanically polished sample in the mixed solution for anodic coating, the conditions of anodic coating are: current 0.1-0.3m / A, voltage 25v, time 150s, temperature 10℃-35℃;
[0128] Step 7, rinsing: the corrosion surface of the sample after the anodic coating is cleaned with water and anhydrous ethanol in turn, and dried;
[0129] Step 8: Metallographic examination: Place the corroded sample under a polarized light optical microscope to observe the metallographic structure morphology. Fig.13 Shown is a schematic diagram of the metallographic structure of the anode coating of this scheme at 100 times the magnification.
[0130] Comparative Example 2:
[0131] Step 1, preparing an anode coating solution: a mixed solution of fluoroboric acid and water, wherein the mixed solution component ratio is 5g:200ml;
[0132] Step 2, sample preparation: use a metallographic cutting machine to take a 5086-H111 aluminum alloy metallographic sample;
[0133] Step 3, inlaying: placing the 5086-H111 aluminum alloy metallographic sample in an inlay mold sleeve, adding hot-inlay phenolic resin inlay material, and inlaying the sample;
[0134] Step 4, grinding: Place the prepared sample on a metallographic grinding and polishing machine for grinding. For aluminum alloy, water-grinded non-silicon sandpaper is preferred. The grits of the grinding sandpaper are 180#, 400#, 800#, 1200#, and 2000#. The subsequent process should be polished to eliminate the wear marks of the previous process;
[0135] Step 5, mechanical polishing: Place the polished sample on a grinding and polishing machine for polishing, use a long-pile cloth for polishing, polish for 8s to 15s, use a diamond polishing agent with a particle size of 1.5μm, and a polishing speed of 900r / min;
[0136] Step 6, anodic coating: using a voltage-stabilized power supply, placing the mechanically polished sample in the mixed solution for anodic coating, the conditions of anodic coating are: current 0.1-0.3m / A, voltage 25v, time 150s, temperature 10℃-35℃;
[0137] Step 7, rinsing: the corrosion surface of the sample after the anodic coating is cleaned with water and anhydrous ethanol in turn, and dried;
[0138] Step 8: Metallographic examination: Place the corroded sample under a polarized light optical microscope to observe the metallographic structure morphology. Fig.14 Shown is a schematic diagram of the metallographic structure of the anode coating of this scheme at 100 times the magnification.
[0139] Comparative Example 3:
[0140] Step 1: prepare conventional aluminum alloy metallographic corrosion Keller reagent, the solution ratio is: hydrofluoric acid 1ml + nitric acid 1.5ml + hydrochloric acid 1.5ml + water 95ml;
[0141] Step 2, sample preparation: use a metallographic cutting machine to take a 5083-H111 aluminum alloy metallographic sample;
[0142] Step 3, inlaying: placing the 5083-H111 aluminum alloy metallographic sample in an inlay mold sleeve, adding hot-inlay phenolic resin inlay material, and inlaying the sample;
[0143] Step 4, grinding: Place the prepared sample on a metallographic grinding and polishing machine for grinding. For aluminum alloy, water-grinded non-silicon sandpaper is preferred. The grits of the grinding sandpaper are 180#, 400#, 800#, 1200#, and 2000#. The subsequent process should be polished to eliminate the wear marks of the previous process;
[0144] Step 5, mechanical polishing: Place the polished sample on a grinding and polishing machine for polishing, use a long-pile cloth for polishing, polish for 8s to 15s, use a diamond polishing agent with a particle size of 1.5μm, and a polishing speed of 900r / min;
[0145] Step 6, corrosion: place the mechanically polished sample in a corrosion reagent for 20 seconds;
[0146] Step 7, rinsing: the corroded surface of the sample after mechanical polishing is cleaned with water and anhydrous ethanol in turn, and dried;
[0147] Step 8: Metallographic examination: Place the corroded sample under a conventional optical microscope to observe the metallographic structure morphology. Fig.15 Shown is a schematic diagram of the metallographic structure of the conventional etching process of this scheme at 100 times.
[0148] pass Figures 1 to 15 It can be seen from the schematic diagram of the metallographic structure that the corrosive agents of Examples 1 to 9 have a good corrosion effect on 5xxx series aluminum alloys, and the grain boundaries and grain sizes are clear and obvious; Comparative Examples 1 and 2 require metallographic equipment with the technical capability of polarized light processing, and the chromatographic color difference in the grain boundary effect is small, and there are limitations in identification; Comparative Example 3 has a poor corrosion effect and cannot display the grain boundaries.
[0149] The above description shows and describes several embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. And the changes and modifications made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.
Claims
1. A 5xxx series aluminum alloy grain boundary metallographic etchant, characterized in that: 1-2g potassium permanganate, 1-2ml hydrofluoric acid, 14-20ml sulfuric acid, 100ml ultrapure water, wherein the mass concentration of hydrofluoric acid is not less than 40%, the mass concentration of sulfuric acid is 95%-98%, and the conductivity of ultrapure water is ≤10μS / cm.
2. A method for displaying the grain size of a 5xxx aluminum alloy using the 5xxx aluminum alloy grain boundary metallographic etching agent of claim 1, characterized in that: The steps include: Step 1, prepare a mixed corrosive agent of 1-2 g potassium permanganate, 1-2 ml hydrofluoric acid, 14-20 ml sulfuric acid, and 100 ml ultrapure water; Step 2, sample preparation: use a metallographic cutting machine to take a metallographic sample of 5xxx series aluminum alloy; Step 3, inlaying: placing the 5xxx series aluminum alloy metallographic sample in an inlay mold sleeve, adding a hot-mounting phenolic resin inlay material, and inlaying the sample; Step 4, grinding: Place the prepared sample on a metallographic grinding and polishing machine for grinding, using sandpaper for grinding. The subsequent process should be polished to eliminate the grinding marks of the previous process; Step 5: Mechanical polishing: Place the polished sample on a grinding and polishing machine for polishing. Use a long-pile cloth for polishing. The polishing time is 8s to 15s. Step 6, corrosion: place the mechanically polished sample in a corrosion reagent for 20s to 30s; Step 7, rinsing: the corroded surface of the sample after mechanical polishing is cleaned with water and anhydrous ethanol in turn, and dried; Step 8: Metallographic examination: Place the corroded sample under a conventional optical microscope to observe the metallographic structure morphology.
3. A method for displaying grain size of 5xxx series aluminum alloy according to claim 2, characterized in that: In the step 2, water-grinded non-silicon sandpaper is preferably used, and the grits of the grinding sandpaper are 180#, 400#, 800#, 1200#, and 2000#, respectively.
4. A method for displaying grain size of 5xxx series aluminum alloy according to claim 2, characterized in that: The diamond polishing agent used in the polishing in step 3 has a particle size of 1.5 μm, and the rotation speed of the mechanical polishing is 900 r / min.